Hypothalamic Regulation of Cardiorespiratory Functions: Insights into the Dorsomedial and Perifornical Pathways - Laura Carrillo-Franco; Marta González-García; Carmen Morales-Luque; Marc Stefan Dawid-Milner; Manuel Víctor López-González (Biology)
The dorsomedial hypothalamus nucleus (DMH) plays a pivotal role in the orchestration of sympathetic nervous system activities. Through its projections to the brainstem and pontomedullary nuclei, it controls heart rate, contractility, blood pressure, and respiratory activity, such as timing and volumes. The DMH integrates inputs from higher brain centers and processes these signals in order to modulate autonomic outflow accordingly. It has been demonstrated to be of particular significance in the context of stress responses, where it orchestrates the physiological adaptations that are necessary for all adaptative responses. The perifornical region (PeF), which is closely associated with the DMH, also makes a contribution to autonomic regulation. The involvement of the PeF region in autonomic control is evidenced by its function in coordinating the autonomic and endocrine responses to stress, frequently in conjunction with the DMH. The DMH and the PeF do not function in an isolated manner; rather, they are components of a comprehensive hypothalamic network that integrates several autonomic responses. This neural network could serve as a target for developing therapeutic strategies in cardiovascular diseases.